Analysis of Village Apparatus Performance Using the Balanced Score Card Analysis Method in Garut Regency - Mila Karmila; Della Fadilah Syabani (Spirit Publik: Jurnal Administrasi Publik, 2026)
This study examines the performance of village government officials in delivering public services in Jati Village, Tarogong Kidul District, using the Balanced Scorecard (BSC) framework, an approach that remains underutilized in village-level governance studies. The research addresses the gap in existing performance evaluations that tend to be administrative, fragmented, and output-oriented. Employing a qualitative descriptive method, data were collected through in-depth interviews with village officials and document analysis, and analyzed across four BSC perspectives: financial, customer, internal processes, and learning and growth. The findings indicate that the implementation of BSC provides a comprehensive assessment of village performance, reflected in improved budget transparency, enhanced service quality, increased community participation, and strengthened institutional capacity of village apparatus. The key contribution of this study lies in demonstrating how BSC can align public service performance with participatory and measurable sustainable development strategies at the village level. This study offers practical implications for strengthening human resources, advancing service digitalization, and replicating the BSC-based performance model in other villages with similar characteristics.